Dos taxones naturalizados en la Península Ibérica presentes en Andalucía Occidental. - Aparicio, Abelardo (Acta Botanica Malacitana, 2003)
Two naturalised taxa in the Iberian Peninsula present in west Andalusia. Plabras clave. Hibiscus, Solanum, Andalucía. Key words. Hibiscus, Solamon, Andalusia.